An overview of apoptosis for computer security - Madihah Mohd Saudi; Woodward M.; Cullen A.J.; Noor H.M. (2024)
Immune system is essential to human body as it protects our bodies from pathogens in an orchestrated manner. From a computational viewpoint, the immune system has much to offer by way of inspiration. Recently, there has been growing interest in the use of natural immune system as inspiration for the creation novel approaches to computational problem. This field of research is referred as Immunological Computation or Artificial Immune System. The use of artificial system computer security is an appealing concept for two reasons. Firstly, the human immune system provides human body with a high level protection from invading pathogens in robust manner. Secondly, current techniques used in computer security are not able to cope with the dynamic and increasingly complex nature of computer systems and their security. This paper introduces the concept of apoptosis for computer security. This term is borrowed from cell biology and designates the programmed cell death. 2008 IEEE.